Gut Microbiota in Dholes During Estrus - Wu, Xiaoyang; Shang, Yongquan; Wei, Qinguo; Chen, Jun; Zhang, Huanxin; Chen, Yao; Gao, Xiaodong; Wang, Zhiyong; Zhang, Honghai (Frontiers in Microbiology, 2020)
The co-evolution of gut microbes and the host plays a vital role in the survival and reproduction of the host. The dhole (Cuon alpinus) has been listed as endangered species by the International Union for Conservation of Nature; therefore, conservation and effective breeding of dholes are essential. Effective estrus can promote reproduction. However, little is known about the relative contribution of estrus in shaping the structure and the functions of fecal microbiota. Here, we investigated the potential association between estrus and the fecal microbiota in dholes using shotgun metagenomic sequencing. We found that the estrus stages in dholes vary significantly in terms of gut bacterial composition and microbiome metabolism and function. Compared with that of non-estrus, adult dholes, the microbiome of estrus adult dholes had a significantly higher abundance of Bacillus faecalis and Veillonella, which play a key role in the synthesis of sex hormones and nucleic acids, energy production, and reproductive cell division. The insulin and energy metabolism-related pathways are significantly enhanced in the gut microbes and the related gluconeogenic enzymes are significantly enriched during estrus. These findings suggest that the structure and metagenome of the fecal microbiome during estrus have a significant effect in promoting estrus in dholes, thus providing a new perspective for dhole conservation.